Nitrification using submerged micro bubbles diffuser in an aeration system - WINARTO, FELIXTIANUS EKO WISMO (2010)
The objectives of this research are to evaluate the effectiveness of the micro- diffuser in enhancing nitrification in wastewater treatment. The nitrification performances of micro- and milli- diffusers were evaluated by measuring NH4-N and NO3-N contents. The experimental values were also compared with the theoretical values derived from the kinetic calculations. Two reactors A and B, of size 140x140x500 mm were constructed using perspex to treat municipal wastewater. Aeration in the reactors A and B was provided using millimeter diffuser and micro diffuser, respectively. The diffusers consisted of perforated aluminium plate to generate millimeter bubbles and sintered porous glass to generate micro bubbles. Compressed air was forced through two parallel flow meters at a flow rate of 2.5 L/min. Biomass for both reactors was acclimatized prior to treating the municipal wastewater in the reactors. Two batch experiments were conducted at 26°C for the biological study and in the estimation of the kinetic parameters for the nitrification. Samplings were conducted at 1 hour, 3 hours, and every 6 hours respectively, until 48 hours for each batch of the experiment. The main parameters tested were NH4-N and NO3-N. The results of the study indicated that ammonia-nitrogen removal was achieved at 90% and 87%, for the micro- and milli- diffusers, respectively. The final average ammonia-nitrogen removal rate was found to be 0.48 mg/L.hr and 0.28 mg/L.hr, for micro and milli diffuser, respectively. The experimental degradation rate also closely follows the theoretical degradation rate with the theoretical degradation rate from 36-48 hrs. of aeration found to be 0.5 mg/L.hr and 0.46 mg/L.hr for micro and milli diffuser, respectively. It can be concluded that the use of micro diffuser can provide higher ammonia-nitrogen removal from wastewater. Keywords: Millimeter diffuser; micro diffuser; NH4-N removal;, NO3–N production; kinetics evaluation